Agrin Involvement in Synaptogenesis Induced by Exercise in a Rat Model of Experimental Stroke. (December 2020) - Zhang, Pengyue; Yang, Liqiang; Li, Guangxiang; Jin, Yaju; Wu, Danli; Wang, Qing Mei; Huang, Peidong
Background: Agrin is a proteoglycan that aggregates nicotinic acetylcholine receptors (AChRs) on neuromuscular junctions and takes part in synaptogenesis in the development of the central nervous system. However, its effects on neural repair and synaptogenesis after stroke are still unclear. Objective: This study aimed to investigate the effects of agrin on neural repair and synaptogenesis after stroke and the effects of exercise on this process in vivo and in vitro. Methods: Exercise with gradually increased intensity was initiated at 1 day after middle cerebral artery occlusion (MCAO) for a maximum of 14 days. Neurological deficit scores and foot fault tests were used to assess the behavioral recovery. Western blotting, immunofluorescence, and electron microscopic images were used to detect the expression of agrin, synaptogenesis-related proteins, and synaptic density in vivo. In vitro, the ischemic neuron model was established via oxygen-glucose deprivation (OGD). The lentivirus overexpressed agrin and CREB inhibitor were used to investigate the mechanism by which agrin promoted synaptogenesis. Results: Exercise promoted behavioral recovery and this beneficial role was linked to the upregulated expression of agrin and increased synaptic density. Overexpressed agrin promoted synaptogenesis in OGD neuron, CREB inhibitor downregulated the expression of agrin and hampered synaptogenesis in cultured neurons. Conclusions: These results indicated that exercise poststroke improved the recovery of behavioral function after stroke. Synaptogenesis was an important and beneficial factor, and agrin played a critical role in this process and could be a potential therapeutic target for the treatment of stroke and other nervous system diseases.